PENGARUH MARKET TIMING TERHADAP STRUKTUR MODAL PADA PERUSAHAAN NON KEUANGAN YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Irsyad Yusfiari; Juanda Juanda (Departemen Manajemen, 2023)
The aim of this research is to find out and analyze the effect of Market Timing on Capital Structure in Non-Financial Companies listed on the Indonesia Stock Exchange in 2015-2019. The object of research is the capital structure and market timing of non-financial companies for the 2015-2019 period with data analysis tools in the study using the multiple linear regression analysis method. This study also uses control variables, namely company size and profitability as measured by (Return On Assets). The results of the study show that market timing, return on assets, and company size simultaneously affect capital structure. Partially, market timing has an effect on capital structure, return on assets has no effect on capital structure, and firm size has an effect on capital structure.